Socio-Economic Resilience of Low-Income Families in Urban Public Housing: A Case Study of Lette District, Makassar - Syamsuar, Syamsuar; Ismail, Ashari; Amandaria, Riri (Pinisi Journal of Sociology Education Review, 2025)
This study aims to describe the socio-economic resilience of families living in Lette public housing in Mariso District, Makassar City, and to examine the efforts undertaken to strengthen that resilience. Employing a qualitative descriptive approach, the research involved participatory observation, in-depth interviews with 22 purposively selected informants, and a review of relevant documents. Data were analysed using the Miles and Huberman (1994) model and interpreted through Keck and Sakdapolrak’s (2013) social resilience framework, which includes coping, adaptive, and transformative capacities. The findings reveal that residents face numerous interrelated challenges, such as poor housing conditions, limited access to education, health services, and stable employment, as well as weak social interaction and inadequate infrastructure. Frequent population mobility and limited social cohesion further undermine their socio-economic resilience. Despite these constraints, families employ various coping and adaptive strategies, including building informal support networks and engaging in mutual assistance. However, their transformative capacity remains low due to weak institutional support and minimal community organization. This study highlights the urgent need for integrated and sustained interventions to improve infrastructure, expand access to essential services, and strengthen community participation, so that public housing can serve not only as shelter but also as a foundation for social and economic empowerment.